2015
DOI: 10.1055/s-0041-102899
|View full text |Cite
|
Sign up to set email alerts
|

Intraokulare Raumforderungen im Kindesalter ohne Retinoblastom

Abstract: The diagnosis of an intraocular mass in children can be challenging as invasive procedures are not allowed, in particular if a retinoblastoma may be present. In eyes with a unilateral tumour mass and loss of function enucleation with subsequent histopathological processing might be the only option to establish a diagnosis and to exclude a malignant tumour. The present paper deals with intraocular tumours other than retinoblastoma in children, with a special focus on the correlation of modern imaging techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Shields et al [14] published their data on 604 cases of so-called pseudo retinoblastomas and found the most common diagnoses to be Coats disease, persistent fetal vasculature, ocular toxocariasis and vitreous haemorrhage. We also analysed 31 cases of advanced stages of unilateral undetermined ocular tumours in childhood treated with enucleation and found the main diagnoses to be Coats disease, astrocytoma, medulloepithelioma or an undetected atypical retinoblastoma [15]. A specific form of the atypical tumour is the so-called diffuse infiltrating retinoblastoma, which is a very rare subtype of this neoplasm and is characterized by its atypical growth pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Shields et al [14] published their data on 604 cases of so-called pseudo retinoblastomas and found the most common diagnoses to be Coats disease, persistent fetal vasculature, ocular toxocariasis and vitreous haemorrhage. We also analysed 31 cases of advanced stages of unilateral undetermined ocular tumours in childhood treated with enucleation and found the main diagnoses to be Coats disease, astrocytoma, medulloepithelioma or an undetected atypical retinoblastoma [15]. A specific form of the atypical tumour is the so-called diffuse infiltrating retinoblastoma, which is a very rare subtype of this neoplasm and is characterized by its atypical growth pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Российский журнал ДЕТСКОЙ ГЕМАТОЛОГИИ и ОНКОЛОГИИ R u s s i a n J o u r n a l o f P e d i a t r i c H e m a t o l o g y а n d O n c o l o g y 2 О р и г и н а л ь н ы е и с с л е д о в а н и я || O r i g i n a l s t u d i e s Введение При односторонней местно-распространенной внутриглазной опухоли с полной утратой зрения энуклеация глаза (ЭГ) может быть единственным методом для установления диагноза и исключения злокачественной опухоли [1].…”
unclassified